Babyland - Chamberlin, Holly, 1962- (Kensington Publishing Corp, 2016)
At thirty-seven, she's never had a one-night stand, crammed for an exam, or made an extravagant purchase. Now she's engaged and preparing for an occasion of her own. But another event just might trump her wedding, one that she and her future husband weren't expecting: Anna is pregnant. From her dress fitting to the timing of the honeymoon, for Anna, one question quickly leads to another--about work, the future--and why she finds herself thinking so much about her colleague, Jack, a tousled, talented artist who is the polar opposite of her comfortingly conventional fiance.